Komposisi dan Sebaran Patotipe Xanthomonas oryzae pv. oryzae, Penyakit pada Padi di Nusa Tenggara Barat - Sudir, Sudir; Yuliani, Dini; Wirajaswadi, Lalu (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
A study was carried out to identify the composition and distribution of Xanthomonas oryzae pv. oryzae (Xoo) pathotypes on rice crop in West Nusa Tenggara, during the 2012 planting season. Three activities were conducted, namely collection of rice leaf samples from the fields, isolation of Xoo from the leaf samples at the laboratory, and testing pathotypes of Xoo at the screen house. Rice leaves showing typical bacterial leaf blight (BLB) symptom were collected from various farmersâ€™ fields. The samples were detached and put into paper envelopes, and were taken to the laboratory for isolation of Xoo, at the Laboratory of Pythopathology of Indonesian Center for Rice Research (ICRR), Sukamandi. Pathotype testing was done in the ICRR screen house by inoculating the leaves of five differential rice varieties using inocula of the Xoo isolates. Resistance of the rice differential varieties was determined based on the BLB disease severity. Inoculated plant with disease severity â‰¤11% was considered resistant (R) and disease severity >11% was susceptible (S). From the 240 samples of rice leaf infected with BLB collected from West Nusa Tenggara, 232 Xoo isolates were obtained. The Xoo pathotype identification showed that pathotype IV was the most dominant in West Nusa Tenggara during the 2012 planting season, numbering 118 isolates or 51.0% out of the total isolates, followed by pathotype VIII (67 isolates or 29.0%), and pathotype III (47 isolates or 20.0%).